Assessment of cytotoxicity upconversion nanoparticles coated by SiO2 on different cell lines - Verkhovskii, Roman A.; Anisimov, R. A.; Lomova, Maria V.; Tuchina, Daria K.; Lazareva, Ekaterina N.; Doronkina, A. A.; Mylnikov, A. M.; Navolokin, Nikita A.; Kochubey, Vyacheslav I.; Yanina, Irina Yu (Proceedings of SPIE)
The present work demonstrates the assessment of cytotoxicity upconversion nanoparticles (UCNPs) coated by SiO2 on different normal and cancer murine cell lines in vitro. The cell viability is scored for cytotoxic effects of UCNPs at dark conditions. UCNPs coated by silica shells provide a dose-dependent cytotoxic effect on all studied cell lines which was most pronounced for the Raw264.7 cell line. It is probably caused by the high phagocytic activity of macrophages. The less sensitive cell line was 4T1. The statistically significant differences in cell viability after 24 and 48 h of incubation of cells with particles were observed just for the macrophage cell line. It is worth notifying that after 48 h of incubation the cytotoxic effect on Raw 264.7 cell line increased which shows a possible negative effect on some subpopulations on blood cells. The obtained results confirm a high sensitivity of the UCNPs to the concentration variations within cells. Carriers based on UCNPs and dyes are promising alternatives to photosensitizer for traditional photodynamic therapy and possess prominent potentials in biological and clinical applications.